SMEs in Regions of Russia: Workers Salary - Pinkovetskaia, Iuliia; Kiseleva, Olga (Journal of History Culture and Art Research, 2018)
This paper aims to explore the impact of factors socioeconomic position of Russian regions on the average wage of employees in small and medium enterprises (SMEs). The present study uses empirical data to obtain new knowledge and estimate the current wages of employees of SMEs in the regions of Russia. It was the data from the official statistical observation of activities of all Russian SMEs for 2015 year. Authors estimated multiple nonlinear regression model on the spatial data. The ratios between wage of employees in SMEs and the subsistence minimum were measured with the use of the function of normal distribution. Studies showed great differentiation of wages of SMEs employees in the regions of Russia. Elaborated instruments for measurement and analysis wages can ensure the development of SMEs in perspective. In order to increase wages, it is necessary to take steps to develop regions and reduce unemployment. Such activities must be carried out by the authorities at the federal and regional levels and included into the development plans of the Russian economy.